Design for 3D printing : scanning, creating, editing, remixing, and making in three dimensions - Bernier, Samuel N.; Luyt, Bertier; Reinhard, Tatiana (Maker Media, 2015)
It's easy to get started with 3d printing, but it takes work to become a great 3d designer. Once you've graduated from downloading other peoples' model and doing simple rudimentary modeling of your own, you're going to want to try your hand at making something beautiful and enduring. This gets you going with professional-level (and free!) design tools, and shows you how to model, scan, and perfect your designs. You'll learn amazing tips and tricks along the way, such as how to make 3D-printed moving models that print in place: take them off the printer, give them a wiggle, and they are ready to move! --Resumé vydavatele
Obsahuje rejstřík
Keywords: trojrozměrný tisk; počítačové tiskárny; trojrozměrné zobrazování; počítačem podporované navrhování; digitální tisk; počítačová grafika; trojrozměrné modelování; three-dimensional printing; computer printers; three-dimensional imaging; computer-aided design; digital printing; computer graphics; three-dimensional modelling; příručky; handbooks, manuals, etc